2014
DOI: 10.1007/8904_2014_339
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic Cardiomyopathy in Pompe Disease Is Not Limited to the Classic Infantile-Onset Phenotype

Abstract: Pompe disease is a genetic disorder caused by a deficiency of acid a-glucosidase

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 18 publications
2
26
0
Order By: Relevance
“…Cardiac tissue staining of subject 15 years of age showed glycogen deposition as shown with PAS staining along with hypertrophy in the presence of LAMP2 mutation. Another interesting study by Lee et al [7] observed and validated the connection put forth in this view point that there is a strong correlation between glycogen storage disease, the Pompe's disease associated with glycogen accumulation and cardiovascular complications like cardiomegaly with features of hypertrophic cardiomyopathy in different subjects between ages 1 year-4 years old. These studies validate the claim that the metabolic abnormalities we perceive in WPW syndrome could result not only because of PRKAG2/AMPK mutation but also other proteins like LAMP2, Phosphorylase kinase and acid glucosidase that could result in similar phenotype with a PRKAG2 mediated WPW phenotype with glycogen accumulation and cardiac hypertrophy (Figure 1).…”
Section: Viewpointsupporting
confidence: 57%
“…Cardiac tissue staining of subject 15 years of age showed glycogen deposition as shown with PAS staining along with hypertrophy in the presence of LAMP2 mutation. Another interesting study by Lee et al [7] observed and validated the connection put forth in this view point that there is a strong correlation between glycogen storage disease, the Pompe's disease associated with glycogen accumulation and cardiovascular complications like cardiomegaly with features of hypertrophic cardiomyopathy in different subjects between ages 1 year-4 years old. These studies validate the claim that the metabolic abnormalities we perceive in WPW syndrome could result not only because of PRKAG2/AMPK mutation but also other proteins like LAMP2, Phosphorylase kinase and acid glucosidase that could result in similar phenotype with a PRKAG2 mediated WPW phenotype with glycogen accumulation and cardiac hypertrophy (Figure 1).…”
Section: Viewpointsupporting
confidence: 57%
“…(48) There is recent evidence that the development of HCM is not limited to the classic infantile-onset disease and that Pompe disease represents a continuum. (49) An interesting recent report also showed the use of ERT for storage caused by a PRKAG2 mutation. (50)…”
Section: Toward Novel Disease-specific Therapeuticsmentioning
confidence: 99%
“…Even in patients without apparent respiratory failure, a subclinical involvement of respiratory muscles has been demonstrated [4]. Minor cardiac conduction abnormalities have also been described [5,6]. Nevertheless, the possible contribution of the impaired cardiorespiratory system to defective exercise performance of these patients has not been studied.…”
Section: Introductionmentioning
confidence: 95%